2023
DOI: 10.28991/cej-2023-09-01-012
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of Crossflow Turbine Configuration Upper Blade Convex and Curvature by Computational Method

Abstract: A pico-hydro-type crossflow turbine (CFT) with an off-grid system configuration is a suitable option to increase the electrification ratio in remote or rural areas because it has a simple shape and can be applied in run-of-river conditions. Yet, a comprehensive study is necessary for the CFT to be applied to run-of-river conditions (low head and extreme fluctuation discharge), since this is categorized as an impulse turbine. One solution to optimize the CFT’s performance in this context is to increase the lift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…This study tries to reoptimize the turbine blades since their thickness is too thick, 8 mm thickness. The modified blades use the 5-mm-thickness acrylic based on the optimal blade design in the prior study [12]. The current CFT design and the blade modification comparison can be seen in Figure 1(a) and Figure 1(b).…”
Section: The Current and Modified Cft Designmentioning
confidence: 99%
“…This study tries to reoptimize the turbine blades since their thickness is too thick, 8 mm thickness. The modified blades use the 5-mm-thickness acrylic based on the optimal blade design in the prior study [12]. The current CFT design and the blade modification comparison can be seen in Figure 1(a) and Figure 1(b).…”
Section: The Current and Modified Cft Designmentioning
confidence: 99%
“…They may be various renewable energy sources using sun, water or wind. Among these sources, the most popular is a small scale wind power [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These turbines can be more efficient and effective on an urban scale, achieving economic and environmental benefits. Adanta et al [21] in 2023, conducted a study to optimize a pico-hydro-type crossflow turbine's performance by curving the upper surface of the blade and increasing the lift force. Their numerical solution results revealed that the upper CFT blade has a parabolic effect on the turbine's performance and specific speed.…”
Section: Introductionmentioning
confidence: 99%
“…Their numerical solution results revealed that the upper CFT blade has a parabolic effect on the turbine's performance and specific speed. They recommended that a CFT with a curved blade is generally more suitable for lowpressure conditions with extreme fluctuations [21].…”
Section: Introductionmentioning
confidence: 99%